Correlates of HIV, STI and TB among sub-Saharan African migrants in Lisbon: a biobehavioral study. (30th September 2020) - Dias, S; Gama, A; Simões, D; Carreiras, E; Mora, C; Ferreira, A P
Abstract: Sub-Saharan African migrants (SAMs) have been disproportionately affected by infectious diseases such as HIV, other sexually transmitted infections (STIs) and Tuberculosis infection (TB). Research on infectious diseases and related factors among migrant populations is critical to further understand these populations' health needs and inform prevention strategies. However, migrants are often underrepresented in national statistics and research. This study aimed to examine correlates of HIV, past STI and past TB among SAMs. A venue-based sample of 790 SSAMs completed a cross-sectional biobehavioral survey on sexual practices, HIV testing and self-reported infectious diseases; an HIV rapid test was offered. Uni- and multivariable logistic regression analyses were performed to examine factors associated with HIV, past STI and past TB. Overall, 5.4% of participants were HIV-positive and 16.7% reported a past STI. Odds of being HIV positive increased by age (OR 1.07, 95%CI 1.03-1.11) and were higher among those who experienced violence from a partner (OR 2.77, 95%CI 1.08-7.10). Increased odds of having a past STI were found among migrants with low income (OR 2.86, 95%CI 1.48-5.56), long-term migrants (>25 years residing in Portugal: OR 2.16, 95%CI 1.06-4.38) and those who reported sexual risk behaviors (≥3 sexual partners: OR 2.06, 95%CI 1.14-3.70; inconsistent condom use: OR 2.61, 95%CI 1.32-5.17). In total, 4.1% of participants had TB in the past; these were more likely male (OR 3.42, 95%CI 1.29-9.06) and HIV positive (OR 11.48, 95%CI 4.55-28.94). Half of the participants had never been tested for HIV before, including over a third of those who had STI or TB in the past. Efforts are needed to reduce missed opportunities for HIV/STIs prevention and uptake of HIV testing among SSAMs through more integrated care, while addressing social determinants of infectious diseases. Key messages: High levels of HIV, STI and TB infection among SAMs were found to be strongly associated with socioeconomic disadvantage and poor living conditions in the host country. Social inequalities are persistently a major factor affecting risk for HIV, STIs and TB, and thus addressing social determinants of infectious diseases must remain a public health priority.